THE EXPERIENCES OF LOCAL TOUR GUIDES IN CENTRAL LOMBOK IN UTILIZING ENGLISH TO AID FOREIGN TOURISTS - Zahratul Fikni; Laila Wati; Rabiatun Adawiah; Muhammad Husnu (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study aims at exploring the experiences of local tour guides in Central Lombok in utilizing English to assist foreign tourists. The research was conducted using a qualitative descriptive method, the data were collected through interviews, observations, and questionnaires involving seven local tour guides in the Kuta Mandalika area. The collected data were then analyzed using qualitative content analysis, which involved organizing and coding the data, identifying emerging themes, and interpreting the findings to draw meaningful conclusions. The results reveal that English plays a crucial role in facilitating communication between tour guides and foreign visitors, enabling them to deliver information about local culture, traditions, and tourist attractions effectively. Furthermore, the study highlights both the challenges and strategies faced by the tour guides in applying English in real-life guiding practices. Overall, these findings emphasize the importance of English proficiency in improving the quality of tourism services and enhancing the experiences of foreign tourists in Central Lombok.